Assessment of the effect of rainfall erosion on radioactive decontamination by analyzing the sedimentary layer formed by soil transported from mountains. Issue 1 (1st January 2018) - Ohnuma, Tohru; Ishii, Keizo
Abstract: The accident at the Fukushima Daiichi Nuclear Power Plant caused widespread contamination in Fukushima Prefecture. The area was mainly contaminated with radioisotopes of iodine 131, cesium 134, and cesium 137. The surface soil has been removed in an attempt to decontaminate the evacuated area (1, 150 km 2 ). Rainfall erosion is believed to decontaminate mountains, so the surface soil has not been removed there. We thus investigated whether the mountains had been decontaminated by analyzing soil from the sedimentary layers found at the mouth of a stream that passes through these mountains. The volumeand radioactivity distributions of the sedimentary layers showed that the heavy rainfall right after the earthquake contained a large amount of radioactive cesium. We confirmed that most small soil particles, those with diameters less than 210 μm, were not deposited at intermediate positions as they were transported downstream. Hence, rainfall erosion is a very effective means of decontaminating the mountains.